Pemanfaatan Gamefikasi dalam Pembelajaran PAI Kelas V di SD Islam Terpadu (IT) Sinar Putih Yogyakarta - Alzahmendhi Alzahmendhi; Lovandri Dwanda Putra; Saddam Muhammad Imaduddin Mu’amar An Naufal; M. Alfiansyah Fiqrullah; Hafidz Muharom (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This research is motivated by the low motivation and activeness of students in Islamic Religious Education (PAI) learning in elementary schools which are still dominated by conventional methods. This condition causes low student involvement and the learning process becomes less interesting. This study aims to describe the use of gamefication in PAI learning for grade V at Sinar Putih Integrated Islamic Elementary School (IT) Yogyakarta, including the form of application, media used, stages of implementation, and its impact on student motivation, activeness, and understanding. The study uses a qualitative approach with a descriptive type. The research subjects consisted of PAI teachers and 20 grade V students. Data collection techniques include observation, in-depth interviews, questionnaires, and documentation. Data analysis was carried out through data reduction, data presentation, and drawing conclusions, with data validity guaranteed through triangulation of sources and techniques. The research results show that gamefication was implemented through interactive quizzes, educational games, a point system, and simple rewards integrated into the opening, core, and closing stages of learning. The use of gamefication had a positive impact on increasing student motivation, engagement, and understanding of Islamic Religious Education (PAI) material. Thus, gamefication is an effective and relevant innovative learning strategy for implementation in Islamic Religious Education (PAI) teaching in elementary schools.